2022
DOI: 10.1111/1750-3841.16246
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella unsaturated fatty acids suppress high‐fat diet‐induced obesity in C57/BL6J mice

Abstract: Chlorella has been identified as a rich source of unsaturated fatty acids. Since the antiobesity effects of unsaturated fatty acids have been well documented; therefore, we explored the antiobesity actions of chlorella unsaturated fatty acids (C.UFAs) in the current study. The obtained results demonstrated C.UFAs, which contain abundant linoleic acid, could retard body weight gain (reducing body weigh by 13.93% after 16 weeks of treatment), improve blood glucose (19.29% lower) and lipid profile (23.45% lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Indeed, the health potential of FAs from C. vulgaris were already addressed in the literature. For instance, in mice fed with a high-fat diet, the administration of FAs from C. vulgaris promoted a beneficial effect on hyperglycemia, hyperlipidemia, hepatic steatosis, and adipocyte hypertrophy [ 38 ]. Another study evaluated the effect of auto- and heterotrophic C. vulgaris in zebrafish and showed that both strains have anti-obesity, anti-steatosis, and anti-inflammatory activity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the health potential of FAs from C. vulgaris were already addressed in the literature. For instance, in mice fed with a high-fat diet, the administration of FAs from C. vulgaris promoted a beneficial effect on hyperglycemia, hyperlipidemia, hepatic steatosis, and adipocyte hypertrophy [ 38 ]. Another study evaluated the effect of auto- and heterotrophic C. vulgaris in zebrafish and showed that both strains have anti-obesity, anti-steatosis, and anti-inflammatory activity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an illuminating study, Regueiras et al [ 37 ] demonstrated the capacity of Chlorella vulgaris and Chlorococcum amblystomatis to modulate lipid metabolism in zebrafish larvae, concurrently mitigating steatosis in HepG2 liver cells burdened with excessive fatty acids. Furthermore, research by Yang and collaborators [ 38 ] revealed that Chlorella unsaturated fatty acids (C. UFAs), rich in linoleic acid, positively influenced body weight (resulting in a 13.93% reduction after 16 weeks of treatment), improved blood glucose levels (a 19.29% decrease), and enhanced lipid profiles (with a 23.45% reduction in triglycerides and an 8.76% decrease in total cholesterol) compared to C57BL/6J mice on a high-fat diet. This notable effect may be attributed to the reduction of hepatic lipid accumulation, achieved through the down-regulation of lipogenic genes (PPARγ, C/EBPα, LPL, aP2, FAS, and SREBP-1c) and the up-regulation of the lipolytic gene (adiponectin), representing a plausible underlying mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that unsaturated fatty acids rich in Chlorella can improve the hyperglycemia and hyperlipidemia caused by HFD diet and the hypertrophy of fat cells, and slow the accumulation of fat in liver cells by downregulating lipopogenic genes and upregulating adiponectin. 40 The improvement of fat vacuole in mice was achieved by activating the AMPK signaling pathway. These data indicated that SLCTs supplementation could effectively ameliorate HFD-induced hepatic steatosis and liver injury.…”
Section: Discussionmentioning
confidence: 99%